Teacher Education Curriculum of North-Eastern Region in the Light of NCFTE, 2009: An Analysis - Dkhar, Balaiada R. (INDIAN EDUCATIONAL REVIEW, 2016)
Education is the development of individual according to his/her needs and demands of society, of which she/he is an integral part. It aims to develop individuality and at the same time assists in the attainment of social efficiency and dynamism. To achieve this goal, education needs to be adopted according to the needs of the society. As the needs and aims of the society change, the entire structure of education transforms accordingly. “Change is the law of nature”, said William Wordsworth. According to the needs of time, the society updates itself and consequently education also changes to keep pace with the society. From the primitive times till today, a great change has taken place in the system of education. The world has entered into an age of information and communication technology which has opened up new and cost effective approaches for expanding the reach to education. The convergence between technology and education has expanded new vistas for social and economic development.